Character Metaphors in George Orwell's Animal Farm - Dian Fajrina (Universitas Syiah Kuala, 2016)
Animal Farm was written by George Orwell in 1944 to criticize the Soviet Union leaders and their administration represented by animal characters. The objective of this study was to find out the resemblances between the character of Soviet Union leaders at the time the novel was written and those depicted in the novel. In analysing the objective of this study, content analysis was used. The data are the dialogues and other information in the novel concerning the metaphors of characters between the Soviet Union leaders of the 20th century and those in Animal Farm. The writer finds out that Jones metaphors Nicholas II, the last Tsar of Russian Monarchy, Old Major with his speech metaphors Karl Marx with his Communist Manifesto, Napoleon as Stalin, Snowball as Trotsky, Squealer as Pravda, the Russian Newspaper at that time, Frederick as German and Boxer as the type of gullibility proletariat. Indeed, George Orwell's timeless work reminds us that totalitarianism could be harmful to one society.